Reversible intermittent flow-injection determination of mercury in sediments and vinasses by cold vapor atomic absorption spectrometry - Neto, José Anchieta Gomes [UNESP]; Zara, Luis Fabrício [UNESP]; Santos, Ademir [UNESP]; Rocha, Julio Cesar [UNESP]; Cardoso, Arnaldo Alves [UNESP] (My University, 1999)
A reversible intermittent flow-injection procedure is proposed for the automated determination of mercury in sediments and vinasses by cold vapor atomic absorption spectrometry, CVAAS. Solutions of sample and stannous chloride are carried by two air streams and sequentially injected into the generator/separator chamber in a segmented asynchronous merging zone configuration. The intermittent flow in the forward direction carries the mercury vapor through the flow cell, and in the backward direction, it aspirates the remaining solution from the vessel to waste. We investigated composition and concentration of reagents, flow rates, commutation times, reactor configuration, and conditions for mercury release. The accuracy was checked by mercury determination in a certified sediment and spiked vinasses and river waters. The system handles about 100 samples per hour (0.50-5.00 μg L-1), consuming ca. 2.5 mL of sample and 50 mg of SnCl2 per determination. Good recoveries (92-103%) were obtained with spiked samples. Results are precise (RSD <3% for 2.5 μg Hg L-1, n = 12) and in agreement with values for certified reference material at 95% confidence level.